Nutrition in remote Aboriginal communities: Lessons from Mai Wiru and the Anangu Pitjantjatjara Yankunytjatjara Lands - Lee, Andy; Rainow, S.; Tregenza, J.; Tregenza, L.; Balmer, L.; Bryce, S.; Paddy, M.; Sheard, J.; Schomburgk, D. (Wiley-Blackwell Publishing Asia, 2016)
© 2015 The Authors. Objective: To examine the impact of efforts to improve nutrition on the Anangu Pitjantjatjara Yankunytjatjara (APY) Lands from 1986, especially in Mai Wiru (good food) stores. Methods: Multiple methods were employed. Literature was searched systematically. In 2012, the store-turnover method quantified dietary intake of the five APY communities that have a Mai Wiru store. The price of a standard market basket of basic foods, implementation of store nutrition policy requirements and healthy food checklists were also assessed in all seven APY community stores at intervals from 2012. Results were compared with available data from 1986. Results: Despite concerted efforts and marked achievements, including decreased intake of sugar, increased availability and affordability of healthy foods (particularly fruit and vegetables) and consequent improvement in some nutrient intakes, the overall effect has been a decrease in total diet quality since 1986. This is characterised by increased supply and intake of discretionary foods high in saturated fat, added sugar and salt, particularly sugar sweetened beverages, convenience meals and take-away foods. Conclusions: The documented improvements confirm that residing in these communities can help Aboriginal residents exert control over key aspects of their food supply. However, the overall findings reflect broader changes to the general Australian food supply, and reinforce the notion that, in the absence of supportive regulation and market intervention, adequate and sustained resources are required to improve nutrition and prevent diet-related chronic disease on the APY Lands. Implications: This study also provides insights into food supply/security issues affecting other remote communities and wider Australia.